Analisis Sinkretisme Agama dan Adat Istiadat Tradisi Appanaung pannganreang pada Masyarakat Di Bontolangkasa Kecamatan Bontonompo Kabupaten Gowa - Sri Wahyuni; Hajrah Hajrah; Andi Fatimah (HUMAN: South Asian Journal of Social Studies, 2023)
Abstract. This study aims to reveal the syncretism that occurs in the process of the pangnganreang appanaung tradition in the Bontolangkasa community, Kec. Bontonompo Kab. Gowa seen from religion. This study uses qualitative research methods with analysis of syncretism theory. Data in this study were collected through interviews, observation and documentation. The validity of the data was obtained from the angulated process using the angulated data source technique and the triangulation technique to assess the credibility of the data by checking the data to the same source using observation and interview techniques. The results of this study are the syncretism that occurs in the process of the appanaung pannganreang tradition in the Bontolangkasa community, Bontonompo District, Gowa Regency from a religious perspective. This study shows that the appanaung pannganreang procession is carried out on the seventh day, the tenth day, the fortieth day, or the hundredth day. If you look at the relationship between this tradition and the Islamic religion, it is actually not contradictory because in Islam we are ordered to give alms, while the appanaung pannganreang tradition is an activity carried out to give alms to people.Keywords: Appanaung pannganreang, Syncretisme.